Putting Nursing Forward Strategies for the Next Millennium - May, Katharyn (Operating Room Nurses Association of Canada Journal, 1998)
Canadian Nursing faces an extraordinary set of challenges and opportunities in the next decade. I will talk about what some of the opportunities are, but mostly I will speak of the challenges.